2015
DOI: 10.1016/j.ijscr.2015.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Unusual case of life threatening subcutaneous hemorrhage in a blunt trauma patient

Abstract: HighlightsKey learning points.Treatment of the shock state while searching for the possible cause is essential in trauma patient.Bleeding into the subcutaneous plane is underestimated cause of hypovolemic shock.Treatment of closed degloving lesions depends on the size and duration of the lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…[ 36 ] Therefore, early diagnosis and management of the lesion is essential to prevent infectious complications and extensive skin necrosis. [ 5 37 38 ] The overall mortality in our series was 12.6%, and ISS and GCS were found to be an independent predictor of mortality in patients with MLL regardless of BMI.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…[ 36 ] Therefore, early diagnosis and management of the lesion is essential to prevent infectious complications and extensive skin necrosis. [ 5 37 38 ] The overall mortality in our series was 12.6%, and ISS and GCS were found to be an independent predictor of mortality in patients with MLL regardless of BMI.…”
Section: Discussionmentioning
confidence: 58%
“…It has been suggested that MLL is a potential risk for surgical site infection (SSI) in patients with acetabular fracture. [ 37 ] In our study, we lack information regarding SSI in cases that underwent surgical treatment for a pelvic fracture. Furthermore, we relied on BMI and not the central obesity which could be a limiting factor of accurate estimation of the definition and impact of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Mao et al reported a lesion located at the upper thigh, which was treated by surgical drainage after a few days 7. Hefny et al reported a case of an extensive hematoma at the flank without contrast extravasation on the CT 5. In this case, percutaneous suction drainage was performed.…”
Section: Discussionmentioning
confidence: 98%
“…Only a few published case reports describe a Morel-Lavallée lesion in the lumbar region, and they are mainly chronic lesions in non-shock patients 3. Only three cases of hemorrhagic shock have been described 5,6,7…”
Section: Discussionmentioning
confidence: 99%
“…Classen et al [ 5 ] reported a case of MLS situated in the lumbar region treated with conservative treatment based on compression using the patient’s own body weight. Hefny et al [ 6 ] reported a case of MLS in the flunk treated by percutaneous suction drainage. Mao et al [ 7 ] reported a lesion located at the upper thigh treated by surgical drainage.…”
Section: Discussionmentioning
confidence: 99%